The real Hoosiers : Crispus Attucks High School, Oscar Robertson, and the hidden history of hoops - McCallum, Jack, 1949- (Hachette Books, Hachette Book Group, 2024)
"For far too long the storyline of Indiana basketball has been dominated by Hoosiers. Framed as the ultimate underdog, feel good story, there has also long been a cultural debate surrounding the film, and The Real Hoosiers sets out to illuminate the narrative absent from the film. This is the story of the real life team that inspired the team that most have long assumed was Hickory High's championship opponent. They were Crispus Attucks, an all Black team playing in the 1950s in a racially divided Indiana. Veteran sportswriter and the bestselling author of Dream Team, Jack McCallum, excavates the history of the Crispus Attucks Tigers. After a crushing loss to Milan High School (the real Indiana team Hickory High is based on) in the 1954 semi-final (not the final), Attucks went on to win back to back Indiana state championships led by a young Oscar Robertson and an African American coach who recognized the seemingly insurmountable challenges of playing basketball in a state that was a bastion not only for the game but also for the Ku Klux Klan. This is much more than a sports story. The history of Attucks is rich, far beyond the basketball court, and filled with cultural influence and importance. The Real Hoosiers replaces a lacuna in the history of Indiana while dissecting the myths and lore of basketball; placing the game in the context of migration, segregation, and integration; and enhancing our understanding of this country's struggle for Civil Rights"--